Assessment of the combined in-plane and out-of-plane behavior of brick infill walls within reinforced concrete frames under seismic loading - Onat, Onur; Correia, Antonio A.; Lourenco, Paulo B.; Kocak, Ali (WILEY, 2018)
Understanding the out-of-plane response of masonry infill walls and preventing their progressive collapse mechanisms is very important for earthquake-prone countries to prevent loss of life and economic loss. In fact, having a realistic collapse mechanism assessment allows suitable prevention measures to be adopted. With this purpose in mind, two full-scale one-bay one-story substructures of reinforced concrete frames (RCF) with infill walls were tested on a shake table. These 2 specimens were designed to represent the response of a typical RC Frame at the fifth floor of an 8-story building, namely the out-of-plane failure of its infill wall under combined bidirectional seismic load. Both specimens were composed of a single-leaf clay brick infill wall surrounded by the RC Frame. However, while the first specimen corresponds to an unreinforced masonry configuration, the second specimen includes horizontal bed joint reinforcement as a strengthening/retrofitting technique. The main novelty of this study is the application of a bidirectional and simultaneous dynamic loading to the specimen, such that in-plane and out-of-plane effects are evaluated together. This work presents several interesting experimental results, with particular emphasis on the bearing capacity of the specimens against out-of-plane failure. As expected, the in-plane capacity of the reinforced infill specimen is larger than that of the unreinforced infill specimen. Nevertheless, the out-of-plane bearing capacities of the two specimens are very similar, in contrast to their ductility capacity, which is significantly increased in the reinforced masonry specimen. The capacities of the two specimens for both in-plane and out-of-plane directions, as predicted by formulations in the literature, are given. The differences found between these calculations and the results of the tests are discussed, and may possibly be explained by the parameters considered in the different formulations.
Keywords: brick infill wall; earthquake; out-of-plane behavior; reinforced concrete; shake table experiment; RC STRUCTURE; TURKEY EARTHQUAKE; SHAKE TABLE; BUILDINGS; Engineering